Mass Deviations From Literary Standards in the Media – Mistakes or New Norms? - Eftimova, Andreana (Media and Language, 2020)
In speech, there are phenomena that deviate from the literary norm and are widely used, ie. represent „mass“ errors that communicators over time stop evaluating as a deviation in their linguistic behavior. Typically, this type of errors is interpreted as a manifestation of a low linguistic culture and as a severe deficiency in literacy. In fact, it is very likely that this is a rule change that has occurred, but has not yet been reflected in the codification documents. The article analyzes mass mistakes in the media that are no longer recognized as defects in speech.
Keywords: mass error; norm; literary language; codification